Consumer Preference for Energy Label in the Purchase Decision of Refrigerator: A Discrete Choice Experiment Approach in the East Coast, Malaysia - Razali, Muhammad Azrin Shah; Kamaludin, Mahirah; Azlina, A.A. (International Journal of Energy Economics and Policy, 2022)
Energy label is a widely used policy instrument to increase consumer awareness of energy-efficient home appliances. It helps consumers make better informed purchasing decision intending to save on the electricity bill. The increase in energy efficiency for a household can generate significant energy savings and emissions reduction which can reduce environmental impact. The energy label targets to fight climate change, protect the environment and is significant to support Sustainable Development Goals (SDGs). This study presents the results of a discrete choice experiment (DCE) on the East Coast, Malaysia to investigate the consumer preferences for energy label in the purchasing decision of a refrigerator. Multinomial logit (MNL) and mixed logit (ML) models are specified to measure the attributes that consumers assess when choosing refrigerators. This study focuses on four attributes, namely energy star, energy consumption, energy saving and refrigerator price. Findings show that consumers have responded positively to the labels, in which about 88.11% of respondents are willing to pay to get better quality appliances that promote a safe environment while 11.89% of respondents are not willing to pay. The findings are useful in improving the effectiveness of existing energy efficiency and labelling programs to accelerate the adoption of energy-efficient technology in Malaysia. Hence, the implementation of energy label promotes energy-efficient appliances, which is in line with SDG Goal 7: Ensuring access to affordable, reliable, sustainable, and modern energy for all.